Pengaruh Likuiditas, Leverage dan Ukuran Perusahaan terhadap Financial Distress pada Perusahaan Properti dan Perumahan - Stephanie Stephanie; Lindawati Lindawati; Suyanni Suyanni; Christine Christine; Efvina Oknesta; Adam Afiezan (COSTING : Journal of Economic, Business and Accounting, 2020)
At present the development of property and housing companies is very rapid. The purpose of this research is to be able to determine the effect of Liquidity, Leverage and Company Size on Financial Distress in Property and Real Estate Companies listed on the Indonesia Stock Exchange Period 2013-2017. The approach used is quantitative research. Researchers use secondary data types and sources. The population of this research is 48 Property and Real Estate Companies listed on the Indonesia Stock Exchange in the period 2013-2017. The sample is 29 Property and Housing Companies listed on the Indonesia Stock Exchange for the period 2013-2017 with 145 observational samples. The sampling technique is a purposive sampling method. Data Analysis Technique used is Logistic Regression. The results of this study are liquidity affecting financial distress in Property and Real Estate companies listed on the Indonesia Stock Exchange. Leverage does not affect financial distress in Property and Real Estate companies listed on the Indonesia Stock Exchange. The size of the company does not affect financial distress in Property and Real Estate companies listed on the Indonesia Stock Exchange. Liquidity, leverage and company size affecting financial distress in Property and Estate companies listed on the Indonesia Stock Exchange. Keywords: Liquidity, Leverage, Company Size and Financial Distress